Ethnobotanical Study of Medicinal Plants Used in Ilam City in Western Iran with Anti-Headache Application - Sharareh Jahangiri; Naser Abbasi; Zeynab Cheraqi; Damoun Razmjoue; Mahmoud Bahmani (Traditional and Integrative Medicine)
Headaches are one of the main causes of disability worldwide and have a negative impact on various aspects of people's lives. Considering inadequate advances in pain management, this ethnobotanical research was carried out to identify medicinal plants for the treatment of headaches within the city of Ilam in western part of Iran. For this purpose, the questionnaires were first distributed to the traditional healers of the city of Ilam, and the regional traditional medical information was collected. The data was analyzed quantitatively and qualitatively. Results showed that medicinal plants including Seidlitzia rosmarinus Boiss., Melissa officinalis L., Dianthus orientalis Adams, Prunus haussknechtii C.K.Schneid. , Isatis raphanifolia Boiss, Cannabis sativa L., Cichorium intybus L., and Prunus lycioides (Spach) C.K.Schneid. were used for treating headache in this region. The most used plant family was the Rosaceae family. The aerial part was the most used part (37%) and decoction was the most traditional method of use. Although some of the plants mentioned are used worldwide to treat headaches, this study recommends using Seidlitzia rosmarinus and Melissa officinalis as analgesic. The identification, isolation, purification, and other pharmaceutical analyses of the biochemical compounds of these plants pave the way for new pharmacological treatments.